Carbon storage and flux in arid soils as an environmental service: An example in northwestern Mexico - Ayala Niño, Fernando; Maya Delgado, Yolanda; Troyo Diéguez, Enrique (REVISTA TERRA LATINOAMERICANA, 2018)
Soil is generally conceived as infrastructure support and medium for agricultural production, while the environmental services soil provides are poorly valued or recognized. Among these services, carbon (C) sequester and storage is a focal point of scientific interest due the large quantity of C the soil stores. The aims of this study are (1) to review the different components, processes and features that are present in dryland soils for C storage; and (2) to estimate soil C flux and content in the arid region of La Paz BCS, northwestern Mexico, through two study cases. Sixteen soil profiles were described and sampled based on representative geomorphology to determine soil organic carbon (SOC) and soil inorganic carbon (SIC) contents. Estimated values of 0.15 to 44.25 Mg ha‑1 for SOC and 0.045 to 28.19 Mg ha‑1 for SIC surpass those reported for the soils of Baja California Sur with 16 Mg ha-1. Values of carbon fluxes after 22 months of monthly measurements were highly variable (-0.058 to 0.828 µmol s-1 m-2). Positive values of soil respiration were registered only after an extraordinary rainy season; negative values may be related to CO2 capture through active photosynthetic organisms such as biological soil crusts which, under specific moisture and temperature conditions and coupled with soil organisms, exhibit evidence of their functioning as C source and sink. The present study contributes to understanding the potential of soils of the arid region of northwest Mexico in providing ES through carbon sequester and increases knowledge of BSC and their function in the soil-ecosystem relationship.